Primary route network proceedings of the conference "Further Developments for a Primary Route Network" organized by the Institution of Civil Engineers and held in London on 4-5 March, 1986. (Telford, 1986)
The focus of these papers is on the primary route network. They provide an industrial view, highlight central and local government policies, discuss the development of France's primary route network over 25 years, look at operational aspects, and conclude by looking at major missing links.